Comparing Nanofiltration and Ion Exchange for Reverse Osmosis Pretreatment in Industrial Water Treatment: A Techno-Economic Analysis - Harwin, Harwin (Graduate School of Universitas Syiah Kuala, 2024)
Water softening is a crucial process in various industrial applications, and the selection of an appropriate system involves balancing technical efficiency, environmental impact, and economic considerations. This paper presents a comprehensive analysis of two prominent industrial water softening systems, Nanofiltration (NF) and Ion Exchanger (IX), through a multidimensional lens. The systems design and sizing were simulated with computer assistance, using the DuPonts WAVE Water Treatment Design Software version 1.82. The technical evaluation, based on simulations, revealed that IX outperformed NF in total hardness removal ( 99%) at the expense of a slight increase in Total Dissolved Solids (TDS). In contrast, NF demonstrated a superior ability to reduce TDS, albeit with lesser total hardness removal. Environmental considerations highlighted trade-offs, with NF generating higher wastewater volumes and IX producing wastewater with highly concentrated TDS, necessitating complex treatment processes. Economically, NF generally incurred higher Total Annual Costs (TAC) at lower total hardness concentrations, while IX became costlier at higher concentrations. A selection chart is introduced to aid decision-making based on economic considerations. This research offers valuable insights for industries seeking an optimal water softening solution, balancing technical efficiency, environmental impact, and economic considerations. The findings provide a nuanced understanding to guide system selection based on specific water quality requirements and economic constraints.